MANAGEMENT OF MANDIBULAR ABSCESS IN PEDIATRIC PATIENT WITH UNDETECTED FRACTURE : A CASE REPORT - Zam, Syarifah Nova Amiza; Fatkhurrohman, Fuad; Fajrin, Aprilia; Qolby, Idzhar; Puji, Ika; Ulin, Aini; Talitha, Divi (Indonesian Journal of Dentistry, 2024)
Background: Submandibular abscess is an inflammation accompanied by pus formation in the submandibular region. Submandibular abscess ranks the highest of all deep neck abscesses. 70-85% of cases caused by dental infections are the most common cases, the rest are caused by sialadenitis, lymphadenitis, oral wall lacerations or mandibular fractures. The aim of this study was to determine the case profile of submandibular abscess caused by undetected mandibular fracture and its treatment.Method: The research method used was descriptive observational method. Data was taken from direct observation during the procedure and secondary data came from the patient's medical record in the oral surgery department of Sultan Fatah Demak Hospital.Outcome: Based on the case report, it was found that the treatment given to the patient had high success with minimal intervention.Conclusion: Submandibular abscess on the right lower jaw has been treated with incision and drainage so that the inflammatory products of anaerobic bacteria in the submandibular space can be removed properly.